E-Book Interactive Problem Based Learning of the History of the Indonesian Nation’s Struggle Material in Science Learning to Improve the Learning Outcomes of Grade V Elementary School Students: Bahasa Indonesia - I Komang Rama Pradipta; Anak Agung Gede Agung; Didith Pramunditya Ambara (MIMBAR PGSD Undiksha, 2025)
The limited use of varied and innovative learning media in Science and Social Studies (IPAS) lessons has negatively impacted students’ interest, conceptual understanding, and learning outcomes. This condition leads to low student engagement during the learning process and difficulties in relating the material to real-life contexts. This study aims to develop and examine the effectiveness of an Interactive E-Book based on Problem Based Learning (PBL) on the topic of Indonesia’s National Struggle History in IPAS lessons to improve the learning outcomes of fifth-grade elementary school students. This is a development research employing the ADDIE model. The research subjects consisted of one subject matter expert, one instructional design expert, one media expert, three students for individual trials, and nine students for small group trials. Data were collected through objective tests and questionnaires using validated instruments. Data analysis techniques included descriptive quantitative analysis, expert validation, and inferential statistical testing through t-tests. The validation results showed an average percentage of 90.56% in the "very good" category and feasible for use. The effectiveness test obtained a tvalue of 11.36, exceeding the ttable value of 2.060, indicating that the Interactive E-Book is effective in improving students' learning outcomes. The findings imply that the developed PBL-based Interactive E-Book enhances active participation, independent learning, and students' critical thinking skills in IPAS learning.